Psychosocial Outcomes from Self-Directed Learning and Team Mindfulness in Public Education Settings to Reduce Burnout - Carol Nash (Societies)
Attaining psychosocial health for learners self-identifying as burned out is challenging. Yet, positive psychosocial outcomes are possible. Learner burnout is reducible if learners accept their and others’ rights to self-direct their learning. This acceptance requires a community that demonstrates team mindfulness. Successful self-directed learning with team mindfulness is possible at diverse academic levels and in various public education settings. The author co-founded three such educational initiatives aiming to reduce burnout in learners. To reveal the results, the author assesses the total works published since 2020 regarding these initiatives, using narrative methodology. Some form of consensus decision-making is imperative for team mindfulness—it may take different forms. For these initiatives to succeed online, a participant-trusted facilitator who takes on the role of an authentic leader is necessary. If one is lacking, the participants may achieve positive psychological outcomes but not the positive social consequences of a decision-making method upholding team mindfulness. In working with burned-out learners, positive sociological outcomes are possible when a group focuses on self-directed learning and has a learning-related team mindfulness goal in common. By summarizing the positive psychosocial effects regarding burnout and outlining the difficulties of these publicly supported programs for self-directed learning, future research directions are suggested on this topic.